Studi Eksperimental Pengaruh Variasi CDI Terhadap Performa Kendaraan Empat Langkah - Didik Sugiono; Aini Lostari; Novi Indah Riani; Aries Kusdyanto (Infotekmesin, 2023)
The ignition system is a system that greatly affects the performance of a vehicle. Capacity Discharge Ignition (CDI) is a component in the ignition system that works to set the right ignition timing, therefore combustion can be maximized. This study aimed to compare the use of a factory CDI with a CDI from another vehicle, namely the 110 cc Shogun, to determine the performance of a 125 cc GL Max motorbike including torque, power, and fuel consumption to efficiency. The data collection was carried out at speeds of 25 km/hour to 65 km/hour for each gear with an increase of 10 km/hour. The results showed that the larger the gear or teeth, the value of torque, power, and efficiency will also increase. The best results were obtained in the 110 cc Shogun CDI variation with respective values of 7.96 Nm, 6.8 pk, and 81.14%. Meanwhile, the value of the most economical fuel consumption is still the standard CDI GL Max 125 cc with a value of 0.12 kg/pk.hour in the highest gear.